The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/mrc.2433
|View full text |Cite
|
Sign up to set email alerts
|

A DFT and AIM analysis of the spin–spin couplings across the hydrogen bond in the 2‐fluorobenzamide and related compounds

Abstract: In 1975 a large number of coupling constants were measured in 2-fluorobenzamide labeled with (15)N. Some of them were assigned to couplings through intramolecular N-H...F hydrogen bonds (HBs). These couplings change dramatically when CDCl(3) is replaced by DMSO-d(6). In this theoretical paper we provide density functional theory (DFT) calculations that justify the existence of a weak HB in the absence of solvent, while solvents that act as HB acceptors break down the intramolecular hydrogen bond (IMHB) of 2-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…The values of the 2h J(F,H) coupling constant increase in the absolute size as the ρ electron density increases. [28] A decrease of the 1h J (N,H) and 2h J(N,N) coupling constants in 1-and 2-Z,Z appears to be connected with a decrease of the ρ H· · ·N and ∇ 2 ρ H· · ·N parameters as compared with 1-and 2-Z,E. In other words, an electronic channel for transmission of the spin-spin information through a hydrogen bridge is depleted on going from the simple to bifurcated hydrogen bond.…”
Section: Aim Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…The values of the 2h J(F,H) coupling constant increase in the absolute size as the ρ electron density increases. [28] A decrease of the 1h J (N,H) and 2h J(N,N) coupling constants in 1-and 2-Z,Z appears to be connected with a decrease of the ρ H· · ·N and ∇ 2 ρ H· · ·N parameters as compared with 1-and 2-Z,E. In other words, an electronic channel for transmission of the spin-spin information through a hydrogen bridge is depleted on going from the simple to bifurcated hydrogen bond.…”
Section: Aim Analysismentioning
confidence: 97%
“…It occurs due to the formation of the intermolecular N-H· · ·O hydrogen bond with the DMSO molecule. [28] The attenuation of the trans-hydrogen couplings in 1-and 2-Z,Z can be supposed to originate from the weakening of the N-H· · ·N bridge as result of the bifurcated hydrogen bonding. In consequence of the weakening, the r(H· · ·N) and r(N· · ·N) distances in 1-and 2-Z,Z become longer in comparison with the molecules 1-and 2-Z,E having simple hydrogen bond.…”
Section: Trans-hydrogen Bond Coupling Constants 1h J(nh) and 2h J(nmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkorta et al [48] have shown by DFT calculations that introducing one solvent molecule (acetone) into a 2-fluorobenzamide calculation retains the intramolecular NH..F hydrogen bond but adding a further solvent molecule breaks the hydrogen bond. The intramolecular NH..F hydrogen bond in the trans form restricts any intermolecular hydrogen bond with the solvent to only one of the NH 2 atoms resulting in ca.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of benzene as solvent, we have calculated the aromatic solvent-induced shifts (ASIS) with a considerable success [188]. In the case of fluorobenzamide (66), we have calculated the effect of water and acetone on the chemical shifts using the 1: 1 and 1: 2 complexes [19]. One can consider the solid state as a special case of solvation; only, instead of solvent there are other molecules in the unit cell.…”
Section: Solvent Effectsmentioning
confidence: 99%